ANALYSIS OF CONTROL ELEMENTS FOR EFFICIENT AND PREDICTABLE MANAGEMENT IN THE DENTAL PRACTICE - Iulian-Costin Lupu; Alice Murariu; Elena-Raluca Baciu; Răzvan Constatin Brânzan; Dana Gabriela Budala; Cătălin-Silviu Tibeică; Cătălin Mircea Ivănescu; Norina Consuela Forna (Romanian Journal of Oral Rehabilitation)
In the context of increasing competition and rising professional and economic demands within the dental field, the control function emerges as a key pillar for achieving efficient and predictable management. This paper analyses the key control elements applicable within a dental practice, with a particular focus on financial components, the quality of clinical procedures and treatments, and human resources. Relevant key performance indicators (KPIs) are highlighted to facilitate the objective evaluation of practice activities. Furthermore, the paper describes strategies and procedures necessary for the implementation of a functional control system. The aim is to provide a solid theoretical foundation and a practical framework for medical managers or dental practitioners seeking to optimize operations and ensure the sustainable enhancement of practice performance.